BREAST CANCER WITH MICROCALCIFICATES: A BIBLIOMETRIC ANALYSIS - Olena Kolomiiets; Roman Moskalenko (Eastern Ukrainian Medical Journal, 2022)
Introduction. Microcalcifications in breast tissue are an important marker of the tumor process and are crucial for early diagnosis of this pathology. Detection of microcalcifications in the breast gland using mammography is of great importance in the diagnosis of breast cancer (BC), especially in the early stages. The presence of microcalcifications in the mammary gland indicates a worse prognosis, mainly due to a higher frequency of lymph node invasion and rapid metastasis. The objective of the paper is the bibliometric analysis and research of data on the pathomorphological characteristics of breast cancer with biomineralization. Materials and methods. The authors searched for information on BC in electronic databases such as PubMed, Scopus, Web of Science, and Google Scholar using key terms such as "breast cancer," "calcification," "microcalcifications". For bibliometric analysis, we used SciVal (Scopus) online platform for monitoring and analyzing international scientific research using visualization tools and modern citation metrics and VOSviewer tool for building and visualizing bibliometric networks. Results. The presence of microcalcifications in the mammary gland correlates with a worse prognosis, especially due to a higher frequency of lymph node invasion and rapid metastasis. It is important to distinguish microcalcifications by type and origin, as they can be an indicator of differential diagnosis of the pathological process in the tissue of the gastrointestinal tract, namely, benign and malignant pathology. We performed a bibliometric analysis of the scientific sources of the Scopus database, which included 924 publications. The main keywords for the bibliometric analysis were "breast cancer", "calcification", "microcalcifications". The results of the analysis indicated that the number of publications on the specified subject had increased over the past 10 years, which showed the relevance of the problem among scientists. Among the most interesting areas, we singled out the papers devoted to the classification of breast cancers, early diagnosis of breast cancer, and classification of biomineral deposits. In order to build and visualize bibliometric networks, we used the VOSviewer publication activity tool. Conclusions. For the period of 1967–2022, we identified 4 chronological stages from the bibliometric analysis results in the Scopus database, which included: 1) radiological methods of research – mammography, 2) pathomorphological assessment of cervical cancer and calcifications, 3) study of BC progression biomarkers, 4) prognostic assessment of BC depending on metastasis and survival. We divided all publications into 6 thematic clusters: 1) classification of biominerals, 2) mammography, 3) physico-chemical composition of calcifications, 3) ductal neoplasia of the breast, 4) biopsy, 5) metastasis of cervical cancer, 6) calcium hydroxyapatite.